Adaptation of a Suitable Model for Peer Tutoring in Indian School Situations - Yadav, Anamika (JOURNAL OF INDIAN EDUCATION, 2015)
Peer tutoring is an alternative classroom arrangement in which students take an instructional role with classmates or other students. Many models have been developed in which students work in pairs (dyads). The present research was intended to adopt a suitable model for peer-tutoring in Indian situations. The pre-test and post-test design was used and the study was conducted on a sample of 100 students from Varanasi district of Uttar Pradesh. It is evident from the analysis that Reciprocal peer-tutoring is more suitable than Classwide and Cross-age peer tutoring models because in this model, each and every student gets a chance to become tutor and tutee. As a result, they are able to understand each others’ problems regarding the learning and are able to help each other.